How not to waste a crisis: a qualitative study of problem definition and its consequences in three hospitals. Issue 3 (July 2019) - Martin, Graham; Ozieranski, Piotr; Leslie, Myles; Dixon-Woods, Mary
Objectives: The prominence given to issues of patient safety in health care organizations varies, but little is known about how or why this variation occurs. We sought to compare and contrast how three English hospitals came to identify, prioritize and address patient safety issues, drawing on insights from the sociological and political science literature on the process of problem definition. Methods: In-depth qualitative fieldwork, involving 99 interviews, 246 hours of ethnographic observation, and document collection, was carried out in three case-study hospitals as part of a wider mixed-methods study. Data analysis was based on the constant comparative method. Results: How problems of patient safety came to be recognized, conceptualized, prioritized and matched to solutions varied across the three hospitals. In each organization, it took certain 'triggers' to problematize safety, with crises having a particularly important role. How problems were constructed – and whose definitions were prioritized in the process – was highly consequential for organizational response, influencing which solutions were seen as most appropriate, and allocation of responsibility for implementing them. Conclusions: A process of problem definition is crucial to raising the profile of patient safety and to rendering problems amenable to intervention. How problems of patient safety are defined and constructed is highly consequential, influencing selection of solutions and their likely sustainability.